Development of thePpricing Strategy of the Enterprise - Xiaodi, Zhao (Kharkiv : V. N. Karazin Kharkiv National University, 2024)
This master's thesis examines the theoretical and practical aspects of developing a pricing strategy at an enterprise, using LLC “Nova Poshta” as a case study. The research explores the essence of pricing strategy, its formation stages, and its impact on enterprise competitiveness. The financial and economic performance of the company is analyzed, along with a comparative assessment of its pricing policy against competitors. International experience in pricing strategies within postal and logistics services is also reviewed. Based on the findings, recommendations are proposed to improve the pricing strategy of “Nova Poshta” LLC in order to enhance operational efficiency and strengthen its market position.

У магістерській роботі досліджено теоретичні та практичні аспекти формування цінової стратегії підприємства на прикладі ТОВ «Нова Пошта». Розглянуто сутність цінової стратегії, етапи її формування та вплив на конкурентоспроможність підприємства. Проведено аналіз фінансово-економічних показників діяльності компанії, а також порівняльне дослідження її цінової політики з конкурентами. Вивчено зарубіжний досвід формування цінових стратегій у сфері поштово-логістичних послуг. На основі проведеного аналізу запропоновано рекомендації щодо вдосконалення цінової стратегії ТОВ «Нова Пошта» з метою підвищення ефективності діяльності та зміцнення конкурентних позицій на ринку.
Розробка цінової стратегії підприємства
Керівник роботи : Каріна Ігорівна Москаленко, кандидат економічних наук, доцент кафедри управління та адміністрування, Навчально-науковий інститут "Каразінська школа бізнесу"
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; цінова політика; price policy; економіка підприємства; economy of the enterprise; менеджмент; management